The Hunting of the Fashion City: Rethinking the Relationship Between Fashion and the Urban in the Twenty-First Century. (15th April 2020) - Gilbert, David; Casadei, Patrizia
Abstract: This paper argues that a focus on the idea of the "fashion city" can prove counter-productive in thinking about the relationship between fashion and urbanism. We suggest four provocations about the "hunt for the fashion city." First, we argue that the hunt for a singular fashion city is misguided, and seek to move away from a model set by a limited number of established fashion capitals. In particular we propose a "field" of fashion city types, an approach that both acknowledges the diversity of relationships between fashion and cities, and recognizes the different paths that cities have taken. Second, we ask for new maps in the hunt for the fashion city, seeing cities as nodes in wider fashion geographies, and arguing for more extensive and complex cartographies of sites and roles of fashion within cities. Third, we argue that the focus on the "fashion city" gives an inappropriate priority to fashion, and ask whether we are better served by thinking about how fashion works in imperial cities, authoritarian cities and neoliberal cities. Finally, we ask whether the "the fashion city" and particularly the relationship between great metropolises and fashion authority has a particular periodization, and whether our quest might shift in the twenty first century to think about the wider systemic nature of fashion urbanization.